2017
DOI: 10.1099/ijsem.0.001793
|View full text |Cite|
|
Sign up to set email alerts
|

Description of two novel members of the family Erysipelotrichaceae: Ileibacterium valens gen. nov., sp. nov. and Dubosiella newyorkensis, gen. nov., sp. nov., from the murine intestine, and emendation to the description of Faecalibacterium rodentium

Abstract: To better characterize murine intestinal microbiota, a large number (187) of Gram-positive-staining, rod- and coccoid-shaped, and facultatively or strictly anaerobic bacteria were isolated from small and large intestinal contents from mice. Based on 16S rRNA gene sequencing, a total 115 isolates formed three phylogenetically distinct clusters located within the family Erysipelotrichaceae. Group 1, as represented by strain NYU-BL-A3T, was most closely related to Allobaculum stercoricanis, with 16S rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 31 publications
1
62
0
Order By: Relevance
“…Of the RUGs that checkM could only resolve to the Bacteria kingdom, we noticed that 31 of them had significant numbers of protein hits to the Solobacterium , Coprobacillus and Kandleria genera, which are all members of the Erysipelotrichales order. Members of the Erysipelotrichales have been isolated from the human 11 , mouse 46 and insect gut 47 and pig manure 48 . We hypothesized that some of the 31 RUGs may represent new clades within Erysipelotrichales .…”
Section: Resultsmentioning
confidence: 99%
“…Of the RUGs that checkM could only resolve to the Bacteria kingdom, we noticed that 31 of them had significant numbers of protein hits to the Solobacterium , Coprobacillus and Kandleria genera, which are all members of the Erysipelotrichales order. Members of the Erysipelotrichales have been isolated from the human 11 , mouse 46 and insect gut 47 and pig manure 48 . We hypothesized that some of the 31 RUGs may represent new clades within Erysipelotrichales .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this abnormal increased Blautia could be rectified with INU supplementation, suggesting that suppression of Blautia may partially contribute to the effectiveness of INU on NAFLD. Ileibacterium , a novel member of the Allobaculum genus found in 2017, was associated with metabolism exerting a vigorous response to dietary changes, eventually showing protective potential for obesity ( Cox et al, 2017 ; den Hartigh et al, 2018 ). We also found that an enrichment of Ileibacterium with HFD administration.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this taxon was found to be highly coated by IgA relative to other members of the gut microbiota in IBD patients [26]. It includes strictly anaerobic or aerotolerant organisms, and members of the Erysipelotrichaceae family can produce palmitic, stearic and oleic acid, fatty acids predominantly [27]. Over accumulation of tissue palmitic acid results in dyslipidemia, hyperglycemia, increased ectopic fat accumulation, increased inflammatory tone via toll-like receptor 4 [28] as well as pro-inflammatory adipokines mRNA expression in macrophages [29].…”
Section: Discussionmentioning
confidence: 99%